Soft Systems Methodology in Education Applying a Critical Realist Approach to Research on Teacher Education - Gilbert, Jenny; Pratt-Adams, Simon (Springer International Publishing : Imprint: Springer, 2022)
XXVI, 381 p. 112 illus.